(untitled) (Research, Society and Development, 2024)
Introduction: Menstrual poverty is a complex, transdisciplinary and multidimensional phenomenon, faced by girls and women around the world due to lack of access to resources, lack of public policies with adequate infrastructure and misinformation to enable them to correctly manage the condition. menstrual hygiene. Considering that menstrual poverty is recognized as a public health problem worldwide, this study aims to address its problem, identifying and analyzing its socioeconomic and cultural implications. Methodology: A narrative review of the literature was carried out, using the LILACS, PubMed, SciELO and GOOGLE ACADÊMICO databases. Results: Menstrual poverty, in addition to affecting the physical and mental health of many people, also preserves and intensifies inequality between genders. Girls stop attending schools when there is a lack of means to take care of their own menstruation, such as inadequate infrastructure and little availability of hygiene products, subjecting them to situations that ridicule and belittle. This reality full of paradigms comes from a history in which visible bleeding was considered synonymous with dirt, impurity and shame. The problem surrounding menstrual poverty is global, as it is clear that billions of women still do not have effective access to basic and personal hygiene. Conclusion: Menstrual education is crucial to addressing menstrual poverty by addressing sexual and reproductive health. It is vital to start dialogue without stigma before the first menstruation, incorporating popular knowledge. Public policies must guarantee a dignified experience during the menstrual period, reducing school absenteeism.